2010
DOI: 10.1007/s11258-010-9854-2
|View full text |Cite
|
Sign up to set email alerts
|

Leaf anatomy and photosynthetic carbon metabolic characteristics in Phragmites communis in different soil water availability

Abstract: To investigate the variations of anatomical and photosynthetic carbon metabolic characteristics within one species in response to increasing soil water stress, leaf anatomical characteristics, gas exchange and the activity of key enzymes in photosynthesis and photorespiration were compared in different ecotypes of Phragmites communis growing in an oasis-desert transitional zone (ODTZ) from swamp habitat (plot 1-3) via heavy salt meadow (plot 4-7) and light salt meadow habitat (plot 8-9) to dune habitat (plot 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…This characteristic provides higher ability in translocating photoassimilates and higher distribution of water in leaves (Sage 2004). Similar data were also found in Phragmites communis subjected to drought (Gong et al 2011).…”
Section: Discussionsupporting
confidence: 81%
“…This characteristic provides higher ability in translocating photoassimilates and higher distribution of water in leaves (Sage 2004). Similar data were also found in Phragmites communis subjected to drought (Gong et al 2011).…”
Section: Discussionsupporting
confidence: 81%
“…1). Previous studies on GLO regulation under drought stress found no consensus, with some finding reduction in GLO activity 11,21 consistent with our results, and others finding an increase in GLO gene expression 22 and protein activity [23][24][25] under drought.…”
supporting
confidence: 88%
“…The PS cells had smaller and fewer chloroplasts than mesophyll cells had ( Figures 1-3). Although some ecotypes of Phragmites communis have recently been reported to have C 3 -C 4 intermediate or C 4 -like traits (Gong et al, 2011;Zhu et al, 2012), the PS cells of our plants had only a few small chloroplasts, as is typical of C 3 grasses (Figures 1(b) and 3 (a)). Under the light microscope, it was not easy to determine the presence or absence of small chloroplasts in MS cells: they were barely visible in E. tsukushiensis (Figure 1(a)) and not visible in P. communis (Figure 1(b)) and L. japonica (Figure 1(c)).…”
Section: Resultsmentioning
confidence: 64%